PENGARUH PROMOSI PENJUALAN DAN SALURAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN FURING PRIMA PADA PT. BIRU INDOKON - Hendra Nazmi (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
PT. Biru Indokon is a network steel distributor with the prime furing brand. The survey results revealed that several months ago problems arose related to sales promotions and distribution channels which caused sales targets to not be achieved as planned by the company. The purpose of this study was to examine and analyze the effect of sales promotion and distribution channels on purchasing decisions. The theory used in this study is the theory of sales promotion, distribution channels, and purchasing decisions. The method used is a quantitative approach, the type of research is descriptive quantitative and the nature of the research is descriptive explanatory. Methods of data collection with interviews and questionnaires. Method of data analysis with multiple linear regression. The population is consumers who buy prime furing as many as 111 people and sampling using a saturated sampling technique. The results of this study indicate that partial sales promotions and distribution channels have a positive and significant effect on purchasing decisions with a significant level of 0.05. Simultaneously, sales promotions and distribution channels have a positive and significant effect on purchasing decisions with a significant level of 0.05. This study concludes is that both partially and simultaneously sales promotions and distribution channels have a positive and significant impact on purchasing decisions for prime furing.